2022
DOI: 10.3390/biomedicines10071755
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Resin-Modified Glass Ionomer Cement Surface Characteristics after Acidic Challenges

Abstract: The aim of the present study was to assess by atomic force microscopy (AFM) the surface roughness of a traditional glass ionomer cement- GIC (Fuji IX GP, GC Corporation, Tokyo, Japan) and a resin modified glass ionomer cement- RMGIC (Vitremer, 3M ESPE, St. Paul, MN, USA) after different immersion regimes on some acidic drinks. Sixteen cylindrical samples having the height of 5 mm and the thickness of 2 mm were obtained from each material and they were divided into two groups: Group I (Fuji IX samples) and Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…However, the difference between the three study groups was statistically non-significant, with p=0.6. These results can be explained by the studies by Nica et al (2022) and Wheeler et al (2019) after immersing samples in Coca-Cola for glass ionomer and compomers and other acidic agents, and no statistically significant difference was seen on microhardness of any restorative material following immersion in the acidic beverages.…”
Section: Discussionmentioning
confidence: 88%
“…However, the difference between the three study groups was statistically non-significant, with p=0.6. These results can be explained by the studies by Nica et al (2022) and Wheeler et al (2019) after immersing samples in Coca-Cola for glass ionomer and compomers and other acidic agents, and no statistically significant difference was seen on microhardness of any restorative material following immersion in the acidic beverages.…”
Section: Discussionmentioning
confidence: 88%
“…However, a higher calcium release may correspond to alterations in the material’s mass and solubility [ 44 , 45 ]. Also, it was shown that the conventional GIC was more affected by an acidic environment when compared to resin-modified GIC [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the maturation stage, which extends to months following the initial setting reaction, various processes take place which result in changes of compressive strength 26 , 49 , hardness 49 – 51 , toughness 26 , 49 , wear performance 49 , and opacity of the restorative 26 . The resultant functional properties of GICs, including their mechanical performance 52 56 , and surface state 57 , 58 , depend on the conditioning environment. Its acidity 54 , 55 , and chemical composition 55 , 59 affect the kinetics of the maturation stage, as reflected in the resultant performance of a GIC.…”
Section: Discussionmentioning
confidence: 99%